Study on effect of gas-liquid two phase physical feature on slug flow in microchannels - Wang, Lin lin (Frontiers in Physics, 2023)
At present, there are relatively few studies on the slug flow generation mode obtained by exchanging gas-liquid two-phase inlets in this paper. In this study, an experimental system combining microfluidic devices and high-speed cameras was used to study the effects of gas-liquid two-phase flow rate, liquid physical parameters, etc. on the characteristic length, generation period and other generation characteristics of slug flow, and dimensionless analysis was conducted to investigate the main factors affecting the characteristic length of gas slug. Results show that the variation range of aeroelastic generation characteristics is the largest when the gas-liquid two-phase flow rate is changed. The surface tension has the least effect on the aeroelastic generation characteristics. Increasing the viscosity can obtain smaller bubbles with shorter generation period, and the aeroelastic characteristic length is 400 μm, and the aeroelastic generation cycle is about 4.5 ms. Through dimensionless analysis, it is found that there is a functional relationship between the characteristic length of aeroelasticity and dimensionless gas-liquid flow ratioQ_*, Reynolds number Re, Weber number We. The characteristic length of aeroelastic can be increased by increasing the gas phase flow rate and decreasing the liquid phase flow rate when the channel size is unchanged. The characteristic length of aeroelastic is affected by inertial force and viscous force during the flow process, while the influence of surface tension can be ignored.